Mogroside IIe Ameliorates Cardiomyopathy by Suppressing Cardiomyocyte Apoptosis in a Type 2 Diabetic Model - Cai, Xin; He, Lingmin; Zhou, Guoao; Li, Shenghua; Liao, Xinghua (Frontiers in Pharmacology, 2021)
Mogroside IIe is primarily present in the unripe fruit of Siraitia grosvenorii (Swingle) C. Jeffrey, and it is the predominant saponin component. The purpose of this study was to investigate the effects of mogroside IIe (MGE IIe) on myocardial cell apoptosis in diabetic cardiomyopathy (DCM) rats by establishing a high-sugar and high-fat diet-induced model of type 2 diabetes (T2D) in SD rats and a homocysteine (Hcy)-induced apoptotic model in rat H9c2 cardiomyocytes. The results showed that MGE IIe decreased the levels of fasting blood glucose (FBG), total cholesterol (TC), triglyceride (TG), and low-density lipoprotein (LDL) levels, but increased the levels of high-density lipoprotein (HDL) in the SD rat model. Furthermore, MGE IIe decreased the levels of lactate dehydrogenase 2 (LDH2), creatine phosphokinase isoenzyme (CKMB), and creatine kinase (CK), and improved heart function. Additionally, MGE IIe inhibited the secretion of interleukin-1 (IL-1), IL-6, and tumor necrosis factor-α (TNF-α), improved myocardial morphology, and reduced myocardial apoptosis in the SD rat model. Furthermore, MGE IIe inhibited the mRNA and protein expression of active-caspase-3, -8, -9, -12, and Bax and Cyt-C, and promoted the mRNA and protein expression of Bcl-2 in the SD rat model. Furthermore, MGE IIe suppressed homocysteine-induced apoptosis of H9c2 cells by inhibiting the activity of caspases-3, -8, -9, and -12. In conclusion, MGE IIe inhibits the apoptotic pathway, thereby relieving DCM in vivo and in vitro.